MONITORING ACTIVITY OF THE CO2 EMISSION OBJECTS SYSTEM COMPONENTS IN FORMATION OF THE AIR MASS IN INDIVIDUAL CLOSED PREMISES - Storozhenko, Dmytro; Dryuchko, Оleksandr; Golik, Yuri; Kytayhora, Кateryna; Gornitsky, Igor; Misko, Anton (Academic journal Industrial Machine Building Civil Engineering, 2019)
According to the developed methodology of the experiment and with the use of electronic devices for measuring the contentof carbon dioxide (CO2) in the air and using a set of special laboratory tools, the following were studied on the example of aschool audience: a) the variety of interactions of the external environment and the subsystem - classroom air; b) the activityof constituent internal objects (present students, plants, absorbent surfaces of structural elements and the interior) in releaseand absorption of CO2, depending on conditions and variation in the action of dominant factors; c) their manifestation and influence on forming the composition and content of the air mass, and therefore the internal microclimate of the classroom,which quality directly affects the health and performance of the present people.
Keywords: room air; CO2 concentration; adaptive microclimate support systems; CO2 emission sources